Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Motivasi Kinerja Guru SDK Kalena Wanno - Angelina Malo; Daud Bulu; Solvila Debora Opa Ora; Asunta Mone; Santi Mali Hawa; Sarianti Lende; Yohanes Lende Bili (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Human resource management is the process of utilizing humans as workers in a humane manner, so that their psychological potential functions optimally to achieve school goals. The indicators in this research that are meant by HR are implementing planning, recruitment and evaluation. Human resources (HR) greatly influence the quality of education in an institution. Educational institutions that prioritize human resources will increasingly support the development of students who are interested in attending that education. This research aims to determine the effect of human resource management on improving the quality of education at SDK KALENA WANNO STATE PRIMARY SCHOOL institutions. This research uses a data collection method through distributing questionnaires directly by distributing questions to respondents and asking them to provide answers to these questions. Respondents in this research are teaching staff at the SDK KALENA WANNO STATE PRIMARY EDUCATIONAL INSTITUTION. The number of questionnaires distributed was 50. The test technique used uses a validity test and a reliability test. Testing the first and second hypotheses uses a simple linear regression test. The research results show that service quality has a positive effect.